Unraveling the potential of cryotolerant Saccharomyces eubayanus in Chardonnay white wine production. (December 2020) - Parpinello, Giuseppina Paola; Ricci, Arianna; Folegatti, Barbara; Patrignani, Francesca; Lanciotti, Rosalba; Versari, Andrea
Abstract: This work investigated the suitability of the cryotolerant yeast Saccharomyces eubayanus to ferment Chardonnay must at different temperatures (10 °C, 12 °C, 16 °C, and 26 °C) over two vintages (2013 and 2014). The effect of added nitrogen was also evaluated. The strain's fermentation parameters (maximum growth rate, lag phase, and asymptotic maximum) and cell growth were compared to the values for two reference Saccharomyces cerevisiae strains. Saccharomyces eubayanus showed its best fermentation performance at low temperatures (10 °C and 12 °C), with optimal kinetic parameters and high sugar consumption. Moreover, wines from the cryotolerant yeast showed a volatile acidity reduction of approximately 50%, and a 9% increase in total polyphenols, compared to the reference yeasts. At 16 °C the cryotolerant and control yeasts performed quite similarly, whereas at 26 °C the former displayed stuck fermentation. For both yeasts, at 10 °C the nitrogen content did not affect maximum growth rate, whereas it did at 16 °C. Sensory analyses were run on the 2014 trials, showing differences in color, sweetness, and overall liking among wines obtained at 10 °C, whereas wines obtained at 16 °C differed only in color. Results demonstrate for the first time the Saccharomyces eubayanus suitability for low-temperature fermentation in white wine production, potentially enriching yeast biodiversity in winemaking. Highlights: S. eubayanus showed good adaptation to low temperature and wines were characterized by low volatile acidity. Nitrogen requirements of commercial and cryotolerant strains were similar. S. eubayanus  wines were characterized by 2-phenethyl alcohol (rose) whereas  S. cerevisiae  by ethyl hexanoate (white fruit). S. eubayanus  is a valuable alternative to conventional yeast in the production of base wine for sparkling wines.